The impact of special exercises to develop the speed of the kinetic response of jumping skill on (horse) among Players of Baghdad education team first AL-Rusafa - Iqbal Ammar Lifta, (International Journal of Psychosocial Rehabilitation, 2020)
The world is witnessing in the current stage a broad scientific rising in all fields, including the sports field, which all its chapters witness this scientific renaissance by the benefit of various studies and researches, In the forefront, the kinetic learning research, which assigns developing individual's physical, skill and motor capacity in order to be able to fulfill the requirements Athletic achievement. Gymnastics activities need strength and speed, because gymnastics has its own physical characteristics. One of these characteristics is the kinetic response that players should have, so horse jumping activity needs speed and strength together. In order for the educational process to be thrives and enhance its results through techniques for using special exercises, learning and education are concepts related to one process which its goal to complete the educational process, develop it, and master it, learning and education have a close link and cannot be separated, learning represents to concepts and principles that belongs to the learner while the education process represent to practical applications of learning concepts. Learning is a complex process that takes a person’s entire life and includes different types of activity and experiences with multiple life situations, It is all what individual seeks to obtain information from different directions, habits and skills, mentally, dynamic or ethical, whether it is this acquisition, subconsciously or non-subconsciously, the complete mastery of the motor skills in gymnastics represents the ultimate goal of motor learning process that is based on reaching the level of players to the highest levels because whatever the level of physical characteristics of player, improvement , development, moral and willful features, it does not achieve the desired results unless all of this is related to the complete mastery of the motor skills represented gymnastic movements on various devices. The motor learning process takes place between brain and muscles, so the brain gives orders (stimuli) to the muscles so these muscles respond to these orders by doing the work (stretching and relaxing), then sends a copy (a picture) of what it has done (movement mastery) to the brain for comparison and errors correction, and thus this process (movement mastery) is done in circle between brain orders and muscle response.